82. Variable tilt-angle, parallel-hole collimation system for molecular imaging gamma tomosynthesis. (December 2018) - Pani, R.; Longo, M.; Pellegrini, R.; Cinti, M.N.; Frantellizzi, V.; De Vincentis, G.
Abstract : Purpose: Nuclear medicine imaging based on commonly used gamma cameras, which are large, bulky and designed for general-purpose imaging, is limited in detecting small lesions often indicative of early stage diseases. To overcome this limitation, the authors propose a gamma tomosynthesis method based on variable tilt-angle collimation system that, complemented by a conventional gamma camera, is able to perform high-resolution three-dimensional imaging. Methods: The variable tilt-angle collimator allows to acquire a set of planar images at different angles, which are then 3D reconstructed through the Shift And Add (SAA) method[1] . Spatial resolutions were measured in reconstructed images using a point source at different source-to-collimator distances; sensitivity was evaluated over the range of slant angles (from −45°to 45°) using a disk source. Image contrast (IC) and contrast to noise ratio (CNR) of sub-centimeters tumours were evaluated using a breast phantom. Furthermore, the capability of the tomosynthesis technique in preserving axial resolution was tested by using the Mini Defrise phantom. Gamma tomosynthesis images were compared with those obtained with a standard circular-orbit SPECT scan. Results: The proposed system allows reaching spatial resolutions in the x-y plane ranging from 9 to 14 mm over a depth range of 6-10 cm; spatial resolution in the depth dimension becomes two times greater than those in the other two dimensions. The measured sensitivity decreased from 9 cps/ μ Ci to 6 cps/ μ Ci varying the slant angle from 5° to 45degr . The IC and CNR resulted from gamma tomosynthesis images demonstrated a significant improvement compared to SPECT. Conclusions: The proposed gamma tomosynthesis demonstrated the potential for superior lesion detection in nuclear medicine imaging. Differently from the currently used SPECT, a conventional gamma camera equipped with the variable tilt-angle collimator could be located at the minimum distance from the patient, thus improving detection, localisation and characterisation of sub-centimetre lesions.